2007
DOI: 10.1143/jjap.46.7603
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Highly Uniform Micrometer-Order-Thick Polycrystalline Silicon Films by Flash Lamp Annealing of Amorphous Silicon on Glass Substrates

Abstract: Polycrystalline silicon (poly-Si) films as thick as 4.5 mm are prepared by flash lamp annealing (FLA) of amorphous silicon (a-Si) films without thermal damage onto glass substrates. The a-Si films are deposited by catalytic chemical vapor deposition (Cat-CVD) at 320 C. Since the hydrogen content in Cat-CVD a-Si films is as low as 3 at. %, they are easily converted to poly-Si without any dehydrogenation treatment. Chromium (Cr) films 60 nm thick are coated onto glass substrates to achieve high area uniformity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 12 publications
3
63
0
Order By: Relevance
“…We have so far investigated the crystallization of a-Si films using flash lamp annealing (FLA), millisecond-order flash discharge from Xe lamps [3,5,6]. Thanks to its proper annealing duration, 4.5 mmthick poly-Si films can be formed on glass substrates without serious thermal damage to entire glass substrates [11,12]. We have also confirmed that the crystallization of a-Si films takes place laterally through explosive crystallization (EC), autocatalytic lateral crystallization driven by the release of latent heat [13].…”
Section: Introductionmentioning
confidence: 99%
“…We have so far investigated the crystallization of a-Si films using flash lamp annealing (FLA), millisecond-order flash discharge from Xe lamps [3,5,6]. Thanks to its proper annealing duration, 4.5 mmthick poly-Si films can be formed on glass substrates without serious thermal damage to entire glass substrates [11,12]. We have also confirmed that the crystallization of a-Si films takes place laterally through explosive crystallization (EC), autocatalytic lateral crystallization driven by the release of latent heat [13].…”
Section: Introductionmentioning
confidence: 99%
“…The surface roughness was controlled by changing RIE processing time. Cr films 200 nm in thickness were formed on the textured glass by sputtering at room temperature for the improvement of adhesiveness [5]. Precursor a-Si films with a thickness of 4.5 mm were prepared on the Cr-coated glass substrates by catalytic chemical vapor deposition (Cat-CVD).…”
Section: Methodsmentioning
confidence: 99%
“…For selective heating of micrometer-thick a-Si without thermal damage to glass, annealing time should be on the order of millisecond, judging from thermal diffusion length of glass and aSi. By using flash lamp annealing (FLA), with millisecond pulse duration, we have succeeded in forming 4.5-mm-thick high quality poly-Si on glass substrates, and also have demonstrated solar cell operation using the poly-Si films [5,6]. Although the crystallization mechanism has already been partially clarified [7], more in-depth understanding will lead to improvement of solar cell efficiency and more productive fabrication processes.…”
Section: Introductionmentioning
confidence: 99%
“…This annealing duration corresponds to the thermal diffusion length of glass and a-Si of approximately 50 µm, meaning sufficient heating of a-Si films a few µm thick, while avoiding thermal damage to glass substrates. We have actually demonstrated that poly-Si films more than 4 µm thick can be formed by FLA even on soda lime glass substrates [8,9], and also succeeded in the operation of solar cells fabricated using the poly-Si films [10]. Furthermore, the crystallization of a-Si films by FLA is found to take place by a unique mechanism, unlike simple solid-phase or liquidphase crystallization, resulting in the formation of unprecedented periodic microstructures.…”
mentioning
confidence: 88%